Managing Innovation in A Supplier Dominated Firm: Considering The Way Forward - Poulsom, Nigel (2007)
One of the most important things to bear in mind when considering innovation is that innovation is essentially change. How that change is managed will determine how innovative a firm actually is and the ability to manage innovation successfully will hopefully lead to a competitive advantage.